Digital Goods Reselling: Implications on Cannibalization and Price Discrimination - Chen, Hongqiao; Chen, Ying-Ju; Li, Yang; Zhang, Xiaoquan (Michael); Zhou, Sean X (Production and Operations Management, 2025)
The resale of used products presents the challenge of cannibalization, particularly pronounced in digital goods markets where perfect substitutes are easily replicable. In this article, we assert that, rather than a threat, resale can serve as an effective pricing tool for managing heterogeneous demand. We consider a seller of digital goods/services who offers a contract to a heterogeneous group of customers at a fixed price for a specified amount of usage allowance. Rather than imposing restrictive sharing barriers, the seller allows subscribers to share their allowances with others in a secondary market. Our analysis reveals that the seller’s optimal strategy involves facilitating resale by eliminating transaction costs. The sharing contract effectively achieves the same outcome as a two-part tariff, wherein subscribers pay an entry fee along with a marginal usage rate. Both approaches generate equivalent revenue and market coverage, and result in idential demand and individual surplus for customers of the same type. Consequently, the sharing contract acts as a mechanism for price discrimination. Our finding provides a new perspective on peer-to-peer resales and also challenges the conventional belief that successful price discrimination hinges on preventing resale.